2019
DOI: 10.1108/jima-10-2018-0188
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of pilgrimage tourism in Indonesia

Abstract: Purpose This study aims to extract information and analyze the antecedents of Muslims following pilgrimage tours. Data from the Central Bureau of Statistics Indonesia shows that 87.18 per cent of the total population of Indonesia are Muslims. In addition to running the ruling of Islam and the pillars of Faith, Muslims also maintain the religious tourism. The form of religious tourism which is widely followed by the Muslims of Indonesia is to follow a pilgrimage to the tomb of the wali (Guardian), both wali lim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 28 publications
0
12
0
3
Order By: Relevance
“…Other scholars have investigated religious tourism such as the motivation aspects of Muslim travelers to choose the destination from Islamic compliance (Rahman et al, 2017) and the extrinsic and intrinsic factors of Umrah travelers' participation in enhancing loyalty (Wu and Mursid, 2019). Using a qualitative study, Handriana et al (2019) have explored pilgrimage tourism in Indonesia from various motivational perspectives. A recent study focused on Umrah travel services has identified the influence of marketing mix include promotion, place, people, product, price, process, physical evidence, marketing communication and after-sales service to predict Umrah travelers satisfaction and loyalty (Othman et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Other scholars have investigated religious tourism such as the motivation aspects of Muslim travelers to choose the destination from Islamic compliance (Rahman et al, 2017) and the extrinsic and intrinsic factors of Umrah travelers' participation in enhancing loyalty (Wu and Mursid, 2019). Using a qualitative study, Handriana et al (2019) have explored pilgrimage tourism in Indonesia from various motivational perspectives. A recent study focused on Umrah travel services has identified the influence of marketing mix include promotion, place, people, product, price, process, physical evidence, marketing communication and after-sales service to predict Umrah travelers satisfaction and loyalty (Othman et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Pada dasarnya, semua agama memiliki perjalanan ziarah keagamaannya masing-masing yang menyelipkan hari bebas agar setelah melakukan perjalanan ziarah, peziarah dapat melakukan perjalanan wisata keliling daerah tersebut (Woodward, 2004). Wisata ziarah religi terutama paket perjalanan khusus muslim memiliki potensi pasar yang cukup besar dan berpotensi untuk dikembangkan (Handriana et al, 2020) Masjid Jami' An-Nawier pun didirikan serta diwakafkan oleh sosok misterius yang dimakamkan pada makam keramat yang terletak di dalam area kompleks Masjid An-Nawier yaitu Syarifah Babah Kecil.…”
Section: Wisata Ziarahunclassified
“…Destinasi wisata adalah suatu kawasan tertentu yang dipilih oleh seorang pengunjung dan dapat tinggal selama waktu tertentu di lokasi wisata dengan berbagai tujuan selain kunjungan wisata (Narotama et al, 2020). Tak jarang umat Islam di Indonesia mempraktekkan wisata religi dengan mengunjungi makam para wali yang tersebar di seluruh tanah air (Handriana et al, 2020) Namun perlu dipertanyakan adakah pengaruh wisata religi terhadap peluang ekonomi rakyat?…”
Section: Pendahuluanunclassified